Innovative strategies and nutritional perspectives for fortifying pumpkin tissue and other vegetable matrices with iron - de Escalada Pla, Marina Francisca (2020)
The present review article focuses on different technological strategies and nutritional perspectives having added advantage to human health in fortifying vegetables matrices with iron. An introduction to the main aspects related to iron deficiency consequences is resumed in order to understand the importance of developing new strategies for improving iron intake. In this sense, the tendencies and alternatives will also be discussed. Emerging technologies like impregnation or dry infusion are presented as sustainable options for obtaining structured fortified vegetables. A review about the usefulness of edible covers for stabilizing micronutrients and/or probiotic microorganisms in fortified matrices is also analysed. Since iron deficiency still continue to be a worldwide health issue, innovating in food fortification remains a challenge for researchers and food manufactures.